The Agreedness between Observation and Self-report Method in Work Posture Analysis - Widyanti, Ari (Jurnal Ilmiah Teknik Industri, 2018)
Work posture analysis plays an important role in providing safe and productive workplace, through minimizing musculoskeletal symptoms or disorders. The postural analysis can be conducted through observation, direct, and self-report method. Each has their advantages and disadvantages. Purpose of this study is to compare obervation and self-report analysis in the context of degre of agreenes. One rater observes and gives rating to the fifteeen work postures in an automotive service company using Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA). In addition, six workers in the automotive service company also fill out the Nordic questionnaire as a self-report of musculoskeletal symptoms or disorders. Descriptive analysis is conducted to compare the musculoskeletal symptoms using both observer and self-report analysis. Results show that RULA is slighlty better than REBA in accordance to the Nordic questionnaire’ result. Implications of the result is discussed.